Perlindungan dan pengelolaan wilayah pesisir sebagai kewenangan daerah - Soediono, Ricardo; Doroh, Gasper; Hidayat, A. Taufiq; Sugiono, Brilian Ahmad (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
This study aims to examine the authority of local governments and to identify an ideal regulatory model for community-based coastal area protection and management. This is crucial as most of these islands are small and rich in natural resources with high economic potential. Ironically, according to data from the World Bank and Statistics Indonesia (BPS), coastal communities remain largely impoverished. The study focuses on two main issues: (1) the extent of local government authority in regulating community-based coastal protection and management, and (2) the ideal regulatory model. Using normative legal research, the findings indicate that local governments hold such authority under laws including the 1945 Constitution, Law No. 1/2014, Law No. 23/2014, and relevant ministerial regulations. The ideal model is a regional legal policy (local regulation) specifically ensuring community participation in managing coastal resources to alleviate poverty and promote justice and welfare.